Original articleCosmetic effect in patients with early breast cancer treated with breast conserving therapy (BCT) and with HDR brachytherapy (HDR-BT) “boost” - Kulik, Anna; Łyczek, Jarosław; Kawczyńska, Maria; Gruszczyńska, Ewelina (Journal of Contemporary Brachytherapy, 2009)
Purpose: The estimation of cosmetic effect in 93 patients with early breast cancer treated with breast conserving surgery (BCS) followed by combined radiotherapy, including HDR brachytherapy (HDR-BT) boost. Material and methods: After BCS (tumorectomy or quadrantectomy) external beam radiation therapy (EBRT) was used in total dose of 50 Gy for the whole breast. Tumor bed was localized basing on clinical and mammographic preoperative examinations and histopathology evaluation. 10 Gy in one fraction was applied to all patients using HDR-BT. Steel interstitial needles stabilized by plastic templates were used. 192-Ir with 10 Ci nominal activity and HDR-GammaMed 12i unit (Mick Radio-Nuclear Instruments, Inc., Mt. Vernon, NY) and ABACUS software were used. 31 patients received additional chemotherapy. Cosmetic effect was evaluated in 36 month after the end of brachytherapy treatment basing on modified EORTC scale. For statistical analysis the rang of correlation test, contingent test, linear regression test and ProbRough rulet induction test were used. Results and Conclusions: HDR-BT tolerance was good in most of the cases. Excellent and very good cosmetic effect was observed in 79 patients (85%). Statistically important correlations between following examined prognostic factors and cosmetics outcome were observed: clinical and mammographic tumor estimation, method of breast conserving surgery, type of skin incision, number of interstitial applicators, irradiated reference volume (PTV) and type of optimization method. No correlations with cosmetics effect were found in factors such as: age of patients, location of tumor or additional therapy.